If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 3y = -9 Solving 10x + 3y = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 10x + 3y + -3y = -9 + -3y Combine like terms: 3y + -3y = 0 10x + 0 = -9 + -3y 10x = -9 + -3y Divide each side by '10'. x = -0.9 + -0.3y Simplifying x = -0.9 + -0.3y
| (5/4)x^2-4=24 | | t=-13+(-3) | | y=2.4x-0.001x^2 | | 2b=90 | | 8sin^2x=5-10cosx | | 4x-8(x+1)=-4x+24 | | 8/m=4 | | .4x+.25(81-x)=30 | | 8(x-7)-3(2x+y)=15 | | x^2-5x+4x=180 | | 5x-25=18-4x+5-3x | | 8senx-3cosx=0 | | Y+15y+36=0 | | 2x+15=-2x-5 | | -3y-9y=4/5 | | 8x^2-5x-8=0 | | 4(y-9)=-6(5+y) | | 6x-52=3x | | 0.66q+0.75=0.5 | | 4(x+3)=-5 | | 8x+15+3x+20= | | 15+y=2y-7 | | 12/35=6/7n | | 7a+25=60+2a | | -14x=-5x+36 | | s-35=20 | | 30r^3+85r^2-70r= | | 6-(2-4x)+5=3(1-3x) | | 27+4x=7 | | 3x-t=2x | | r+31=-3(1-6r) | | -2(-2x+3)=-10x-8 |